Adoption of improved fallows in West Africa: lessons from Mucuna and Stylo case studies - Tarawali, G.; Carsky, R.J.; Manyong, Victor M.; Vissoh, Pierre V.; Osei-Bonsu, P.; Galiba, M. (1999)
Traditional shifting cultivation systems can no longer be sustained in West Africa because of rapid increases in human and livestock populations. Short-duration, improved fallows are among the alternative land-management strategies that have evolved. This paper reviews how velvetbean or mucuna (Mucuna pruriens) and stylo (Stylosanthes hamata and Stylosanthes guianensis) management systems were developed and disseminated in West Africa. Mucuna was first adopted by farmers in southwestern Benin between 1988 and 1992, and the number of testers of the innovation rose to 10,000 farmers throughout Benin by 1996. Suppression of spear grass (Imperata cylindrica) was perceived as the main benefit of mucuna fallows. The stylo technology was introduced in the late 1970s, and it was primarily targeted to livestock production in the subhumid monomodal rainfall zone. The uptake of stylo has been relatively slow and modest in West Africa in contrast to the faster rate of adoption of mucuna in southwestern Benin. Some of the contributory factors to the slower adoption of stylo than mucuna include rainfall regime, lack of motivation of livestock keepers, insecure land tenure, limited capability and facilities of extension staff, poor communication among scientists, and unsatisfactory establishment of the crop. Recommendations to increase the adoption of improved fallows include the use of a participatory approach in problem identification, expansion of the genetic base of cover crops for use in fallows, optimization of the multiple benefits of cover crops, management of the improved system, promotional strategies, and appropriate policies.